Nitrogen use efficiency of silage corn with contrasting nitrogen fertility sources in a semi-arid system - Miller, Phearen; Kakkar, Avneet; Norton, Jeanette M. (Frontiers in Agronomy, 2025)
Silage corn production in semi-arid environments poses challenges for sustainable intensification and soil health due to the removal of aboveground biomass during harvest. A nine-year field study in northern Utah, USA, evaluated the effects of different nitrogen (N) fertility sources on silage yield, nitrogen use efficiency (NUE), and soil total nitrogen (STN). Treatments included no fertilizer (Control), ammonium sulfate at two rates (112 and 224 kg N ha-1 year-1; AS100 and AS200), and steer manure compost (224 kg total N ha-1 year-1). Compost increased STN by 23% compared to synthetic fertilizer treatments but produced 31% lower yields than AS-based treatments. While AS100 and AS200 yielded similarly, AS100 exhibited superior NUE. Despite lower yields and NUE under compost treatment, compost contributed to higher STN. These findings suggest that farmers should integrate compost applications with reduced nitrogen fertilizer rates and adopt additional soil health practices, such as crop rotation and cover cropping, to enhance sustainable soil fertility management in silage corn.